COMPUTATIONAL FLUID DYNAMICS (CFD) SIMULATION OF SAND DEPOSITION IN PIPELINE - KINAN, AZRIE (IRC, 2017)
Past reviews have demonstrated that transportation of reservoir fluid through pipeline is one of the most cost effective options for delivering the feed to the processing facility. However, most of the time sand particles are co-produced with the fluids. This will lead to sand deposition on the bottom of the pipeline whenever the transporting fluid velocity is below the critical velocity required. To prevent this from happening and ensure flow assurance, it is crucial to measure and identify the critical velocity. This study presents the results obtained from computational fluid dynamics (CFD) simulation for identifying critical velocity where the formation of static sand bed occurs. The critical velocity is found to be fairly influenced by the sand volume fraction. It was observed that formation of sand dunes occur at the bottom of the pipe at low fluid velocity. The result from the simulations is compared with other studies for validation and analytical comparison.